1999
DOI: 10.1073/pnas.96.3.805
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C1 protein: Obligatory roles for N-terminal domains and lysosomal targeting in cholesterol mobilization

Abstract: Niemann-Pick type C (NPC) disease is an inherited lipid storage disorder that affects the viscera and central nervous system. A characteristic feature of NPC cells is the lysosomal accumulation of low density lipoproteinderived cholesterol. To elucidate important structural features of the recently identified NPC1 gene product defective in NPC disease, we examined the ability of wild-type NPC1 and NPC1 mutants to correct the excessive lysosomal storage of low density lipoprotein-derived cholesterol in a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 28 publications
8
105
0
Order By: Relevance
“…2), in agreement with a previous report (15) where deletion of the C-terminal 4 amino acids of the cytoplasmic tail ablated NPC1 location and function. Inspection of the sequence surrounding the dileucine motif revealed that the C-terminal 8 amino acids of the tail contains a di-acidic sequence (ERE) conforming to the DXE motif proposed to elicit efficient COPII-mediated ER export of certain transmembrane proteins (18, 26 -29).…”
Section: Targeting Of Npc1 To Late Endosomes 48216supporting
confidence: 82%
See 2 more Smart Citations
“…2), in agreement with a previous report (15) where deletion of the C-terminal 4 amino acids of the cytoplasmic tail ablated NPC1 location and function. Inspection of the sequence surrounding the dileucine motif revealed that the C-terminal 8 amino acids of the tail contains a di-acidic sequence (ERE) conforming to the DXE motif proposed to elicit efficient COPII-mediated ER export of certain transmembrane proteins (18, 26 -29).…”
Section: Targeting Of Npc1 To Late Endosomes 48216supporting
confidence: 82%
“…It is composed of 13 transmembrane domains and a small cytoplasmic tail (14) that has been suggested to be essential for the transport of newly synthesized NPC1 to the late endosome (15). Examination of this cytoplasmic tail (numbered 1-27 from Gly 1252 ) reveals several potential late endosome targeting regions, such as a dileucine motif at positions 24 and 25, a tyrosine at position 16, a cysteine at position 10, and a putative ER maturation signal 20 ERE 22 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A trafficking pathway for delivery of nutrients and metabolites between astrocytes and neurons is supported by previous studies. Astrocytes have been implicated in the delivery of glucose and lactate to neurons (19) and are known to play an important role in the uptake and recycling of neuronally released glutamate (20). In this respect it is of interest that glutamine synthetase in human cerebral cortical astrocytes is localized in a manner that closely resembles the perisynaptic astrocytic localization of NPC1 in this study (16).…”
Section: Discussionmentioning
confidence: 76%
“…CLSM was performed 20 h after transfection using a 25 ϫ 0.8 NA oil immersion objective. Filipin staining was performed as described previously (Watari et al, 1999) on fixed cells expressing DiHcRED-MAL by using 5 g/ml filipin.…”
Section: Cholesterol Loading and Filipin Stainingmentioning
confidence: 99%